Struktur, Komposisi Jenis Pohon dan Nilai Ekologi Vegetasi Kawasan Hutan di Kampung Sewan Distrik Sarmi, Kabupaten Sarmi - Floriana Kabelen; Maklon Warpur (Jurnal Biologi Papua, 2009)
This study was to obtain the description of tropical lowland forest of Papua in Sewan village, Sarmi District, Jayapura region. The main objective was to investigate the structure, species composition and ecological value of the forest vegetation. Research methods included line transect, documentation, interview and literature review. Index Shannon Wiener was used to determine the level of species diversity. The results revealed that 27 tree species that grouped into 17 families inhabited the study area. The density of trees was 209 individuals/ha. A number of saplings were identified into 17 species and grouped into 15 families with the density 104 individuals/ha. At the tree level, species with the high important value (IV) index. important value (IV) index were Pometia pinnata Forst. (54.31%), Macaranga gigantea M.A. (45.33%), Knema sp. (27.37%), Nauclea orientalis L. (20.69%), Intsia palembanica Miq. (13.86%), and the other species had lower INP. At the saplings level species that had high INP were Pometia pinnata Forst. (84.05%), Horsfieldia sylvestris Warb. (34.87%), Knema sp (25.92%), Celtis nerifolia (22.54%), and Pterocarpus indicus Willd. (18.12%). Diversity index at tree level and saplings level were 2.73 and 1.91 respectively, and this showed the high diversity of the trees compared to that of the saplings. The ecological value of the forest in Sewan village included the function as watershed area, buffer zone for the wildlife and as habitat for several fauna especially birds and bats. Key words: analysis of vegetation, species of trees, Sewan village, Sarmi.